Registration of 'Sprinter' Hard Red Winter Wheat. Issue 2 (27th March 2015) - Carter, A. H.; Kidwell, K. K.; DeMacon, V.; Balow, K. A.; Shelton, G. B.; Higginbotham, R. W.; Chen, X. M.; Engle, D. A.; Baik, B.; Morris, C. F.
Abstract : High grain protein concentration and stripe rust (caused by Puccinia striiformis Westend. f. sp. tritici Eriks.) resistance are important traits for hard red winter wheat ( Triticum aestivum L.) cultivars produced in the Pacific Northwest region of the United States. The objective of this research was to develop an adapted winter wheat cultivar that can consistently attain the desired level of grain protein concentration combined with effective stripe rust resistance. 'Sprinter' (Reg. No. CV‐1106, PI 671896) hard red winter wheat was developed and released in August 2012 by the Agricultural Research Center of Washington State University. Sprinter was tested under the experimental designations KKHR05001, KKHR05‐0‐0‐0‐97, and WA008118, which were assigned through progressive generations of advancement. Sprinter is a standard height cultivar adapted to low to intermediate rainfall (<400 mm of average annual precipitation), unirrigated wheat production regions of Washington. Sprinter has high‐temperature, adult‐plant resistance to the stripe rust pathogen, high grain protein concentration, and high volume test weight, with excellent end‐use quality properties similar or superior to those of 'Farnum', 'Finley', and 'Bauermeister'.